Biological characteristics of two mesenchymal stem cell cultures isolated from the umbilical cord and adipose tissue of a neonatal common hippo (Hippopotamus amphibius). (August 2022) - Wei, Jinpu; Dong, Xiuxiu; Wang, Bo; Wu, Yajiang; Chen, Wu; Hou, Zhijun; Wang, Chen; Wang, Tao
Abstract: Mesenchymal stem cells (MSCs) are multipotent adult stem cells and can be isolated from many tissues of the body. Due to their potentials to treat various diseases and be applied in animal breeding, MSCs have been isolated and identified regarding their biological properties. Common hippos ( Hippopotamus amphibius ) are a vulnerable species and yet the cryopreservation of their genetic materials is scare. In this study, we successfully established two MSC cultures (UC-MSCs and AT-MSCs) from the umbilical cord and adipose tissue of a neonatal common hippo and comparatively described their features. Both UC-MSCs and AT-MSCs showed fibroblastoid morphology and could be continuously passaged for over 17 passages without dramatic signs of senescence. The cell cultures had normal chromosome composition, say, 17 pairs of autosomes and 1 pair of X chromosomes. UC-MSCs and AT-MSCs displayed similar gene expression profiles. They were positive for CD34, CD45, CD73, CD90 and CD105 and negative for HLA-DR. They demonstrated stemness maintenance by expression of classical stem cell markers. UC-MSCs and AT-MSCs manifested different differentiation potentials into other cell lineages. In summary, these two cell cultures demonstrated the essential properties of mesenchymal stem cells and might play a role in the future research. Graphical Abstract: ga1 Highlights: Two mesenchymal stem cell cultures were established from the common hippo tissues. Dramatic morphology change of the cells as passages increase was not observed. The cell cultures proliferated rapidly and had normal chromosome composition. Cell cultures of different tissue origins showed similar gene expression profiles. Two cell cultures had varying capacities of differentiation into other cell lineages.